A DAP12‐Dependent signal promotes pro‐inflammatory polarization in microglia following nerve injury and exacerbates degeneration of injured neurons. Issue 6 (17th February 2015) - Kobayashi, Masaaki; Konishi, Hiroyuki; Takai, Toshiyuki; Kiyama, Hiroshi
Abstract : Under pathological conditions, activated microglia play paradoxical roles and could have neurotoxic or neuroprotective effects. However, the signal determining how activated microglia affects the fate of neuronal cells remains largely unknown. Here we demonstrate that DNAX‐activating protein of 12 kDa (DAP12), a transmembrane adaptor protein that contains an immunoreceptor tyrosine‐based activation motif, is a critical regulator of microglial function after nerve injury. In a model of mouse hypoglossal nerve injury, the duration of microglial increase after nerve injury became shorter in mice lacking DAP12, although microglial morphology and total cell numbers were not significantly affected during early phase after nerve injury. Intriguingly, expressions of M1‐phenotype markers including pro‐inflammatory cytokines were suppressed in DAP12 ‐deficient microglia. Furthermore, axotomy‐induced motor neuron death was markedly prevented in DAP12 ‐deficient mice. Collectively, DAP12‐mediated microglial activation following axotomy promotes pro‐inflammatory responses, and thereby accelerates nerve injury‐induced neuron death, suggesting that DAP12 is a potential therapeutic target for the protection of neuronal degeneration caused by microglial activation. GLIA 2015;63:1073–1082 Main Points: A DAP12‐mediated signal in microglia promotes expressions of M1‐phenotype markers after nerve injury and prolongs microglial activation. Deficiency of DAP12‐mediated 9 signal in microglia suppresses injury‐induced neuron death.